Lin28 regulates thymic growth and involution and correlates with MHCII expression in thymic epithelial cells - Xiao, Shiyun; Zhang, Wen; Li, Jie; Manley, Nancy R. (Frontiers in Immunology, 2023)
Thymic epithelial cells (TECs) are essential for T cell development in the thymus, yet the mechanisms governing their differentiation are not well understood. Lin28, known for its roles in embryonic development, stem cell pluripotency, and regulating cell proliferation and differentiation, is expressed in endodermal epithelial cells during embryogenesis and persists in adult epithelia, implying postnatal functions. However, the detailed expression and function of Lin28 in TECs remain unknown. In this study, we examined the expression patterns of Lin28 and its target Let-7g in fetal and postnatal TECs and discovered opposing expression patterns during postnatal thymic growth, which correlated with FOXN1 and MHCII expression. Specifically, Lin28b showed high expression in MHCIIhi TECs, whereas Let-7g was expressed in MHCIIlo TECs. Deletion of Lin28a and Lin28b specifically in TECs resulted in reduced MHCII expression and overall TEC numbers. Conversely, overexpression of Lin28a increased total TEC and thymocyte numbers by promoting the proliferation of MHCIIlo TECs. Additionally, our data strongly suggest that Lin28 and Let-7g expression is reliant on FOXN1 to some extent. These findings suggest a critical role for Lin28 in regulating the development and differentiation of TECs by modulating MHCII expression and TEC proliferation throughout thymic ontogeny and involution. Our study provides insights into the mechanisms underlying TEC differentiation and highlights the significance of Lin28 in orchestrating these processes.